Investigation of Ca, Zn, Mg, Fe and Cu concentrations in blood and milk of cows with negative and positive CMT results - Yildiz, H; Kaygusuzlu, E (Natl Veterinary Research Inst, 2005)
The study was performed on 15 healthy and 21 with subclinical mastitis cows, aged 3-5 years. Forty-one udder quarters which gave negative reaction in California Mastitis Test (CMT) were considered to be healthy, and those (n=56) with +1 and +2 reactions in CMT were diagnosed to be affected by subclinical mastitis. Contents Ca, Zn, Mg, Fe, and Cu in blood serum and milk samples were determined by atomic absorption spectrophotometry. Ca levels in the milk serum of the CMT positive cows were significantly lower (P < 0.001) than those found in healthy milk samples. It was also determined that levels of Zn and Fe (P < 0.05 and P < 0.01, respectively) in milk were elevated in the CMT positive cows compared to the controls. Milk serum Mg values did not significantly change. Ca levels of blood serum obtained from healthy cows were higher (P < 0.01) and Cu values lower (P < 0.001) than those found in the CMT positive cows. Serum levels of Mg, Zn and Fe were not significantly altered. Ca levels in milk samples with a CMT result of +1 were significantly higher than those with +2 (P < 0.05). However, it was observed that serum values of Mg, Zn and Fe did not well correlate with CMT scores. In conclusion, the presented results have shown that Ca levels in milk from quarters with subclinical mastitis were lower and Zn and Fe levels higher than those in the controls.
Keywords: cows; subclinical mastitis; Ca; Zn; Mg; Fe; Cu